The Good Daughter - Book 1 - Slaughter, Karin 1971- (New York William Morrow, an imprint of HarperCollinsPublishers, 2018)
Twenty-eight years ago, Charlotte and Samantha Quinns happy small-town family life was torn apart by a terrifying attack on their family home. It left their mother dead. It left their father devastated. And it left the family fractured beyond repair, consumed by secrets from that terrible night. Twenty-eight years later, Charlie has followed in her fathers footsteps to become a lawyer herself -- the ideal good daughter. But when violence comes to Pikeville again, Charlie is plunged into a nightmare. Not only is she the first witness on the scene, but its a case that unleashes the terrible memories shes spent so long trying to suppress. Because the shocking truth about the crime that destroyed her family nearly 30 years ago wont stay buried forever.
Keywords: Murder victims families -- Fiction; Family secrets -- Fiction; Home invasion -- Fiction; Public defenders -- Fiction; Murder -- Investigation; Fiction; Suspense fiction